Aquatic habitat response to small dam removal demonstrates recovery in three years - Jeremy Dietrich; Alison Rickard; Suresh A. Sethi; Scott Cuppett; Patrick Sullivan (Ecosphere)
Abstract Dams disrupt river networks by interrupting longitudinal transport of sediment and nutrients and obstructing the movement of aquatic organisms. Increasingly, water resource managers are looking for dam removal as a solution to restore connectivity and improve aquatic habitats, water quality, and fish passage. Empirical studies on small dams (<7.5 m) that incorporate both ecological and geomorphic monitoring over longer time periods (3 year+ post‐removal) are rare, limiting the data available to restoration stakeholders to inform barrier removal prioritization decisions. To help address this gap, we implemented a suite of geomorphic, biological, and water quality monitoring efforts to assess the effect of a small dam (3.7 m) removal project in the Hudson River Estuary watershed, New York State (USA). We monitored the site prior to removal and continued observations for three years post‐removal to assess differences in ecological conditions between the upstream impoundment and downstream tail‐reach before and after dam removal. Instream sediment composition and mean particle size were highly disparate between upstream impoundment and downstream tail‐reach areas prior to the dam removal but became more uniform and of higher habitat quality across the study site within two years after removal. Functional diversity, taxonomic diversity, and taxa richness of the macroinvertebrate community improved dramatically in upstream habitats within one year of the dam removal, and differences between the upstream and downstream reaches disappeared by the third year after removal, suggesting rapid recovery of stream conditions in the previously dammed upstream reach. Upstream aquatic habitat designations improved within two years from being “moderately impacted” to “slightly impacted,” rising above the biological impairment threshold according to New York State's Biological Assessment Profile score. This allowed both New York and the Environmental Protection Agency to document water quality improvements as a Type‐3 nonpoint source success story. Combined, results from this temperate watershed show that dam removals may provide aquatic ecosystem recovery in relatively short time frames.